DYNAMICS AND CPUE OF FISHING TOOLS IN CONSERVATION AREA CATCH FISHERIES MANAGEMENT AROUND THE BATANG BUNGO RIVER, BUNGO DISTRICT, JAMBI PROVINCE - Hertati, Rini (Asian Journal of Aquatic Sciences, 2022)
CPUE (Catch per Unit Effort) of fishing gear needs to be studied and analyzed for the sustainability of capture fisheries along the Batang Bungo River in the future. The research was conducted from April to May 2022. The purpose of the study was to see the dynamics and calculate the CPUE value of fishing gear along the Batang Bungo River, Bungo Regency, Jambi Province. The research method used is the survey method, determining the research location using purposive sampling method. Research results Fishing gear in the Batang Bungo River Conservation Area consists of seven types of fishing gear, namely: gill nets, traps, Tekalak, Sukam, stocking net, Tajur fishing rods, fishing rods, pulleys and shoots. Identification of fishing gear shows that fishing gear in the Batang Bungo River conservation area has five groups, namely fishing gear, gill nets, traps, fishing gear and fishing gear, and fall fishing gear. The fishing gear that dominates more than 50% is from the fishing line group by 55%, followed by gillnet (17%), traps (15%), falling fishing gear (9%) and grappling and injury (4%).